Refugees from Inside the System: Iraqi Divorcees in Jordan - MacDougall, Susan (Refuge: Canada's Journal on Refugees, 2021)
Based on fieldwork with Iraqi women who married and then divorced Jordanian men and are now registered refugees in Jordan, this study explores the relationship between marriage and immigration laws and refugee status for Iraqis in the country. The legal systems effectively fence the divorced women in, with child custody laws preventing them from leaving and citizenship laws preventing them from securing long-term residency. Jordan’s citizenship and immigration laws collude with family law traditions that assume women’s dependence on their husbands to magnify divorced Iraqi women’s social exclusion. As Iraqi refugees extend their stays in the country, Jordan’s “guests” and their needs have become part of the domestic social landscape; structural refusal to acknowledge their presence contributes to their isolation and invisibility. This case suggests that citizenship laws that differentiate between men and women create gendered refugees as well as gendered citizens.